P3 COPD causation; an assessment of agreement between expert clinical raters. (16th November 2010) - Darby, AC; Barraclough, R; Burge, PS; Hopkinson, NS; Hoyle, JL; Lawson, RA; Niven, RM; Stenton, SC; Warburton, CJ; Barber, CM; Blanc, PD; Curran, AD; et al.
Abstract : Introduction and Objectives: Epidemiological studies consistently find that up to 15% of COPD is attributable to occupational exposures. Despite growing recognition that such exposures are associated with COPD, very little is known about how clinicians weight such attributions against cigarette smoking causation in individual cases. Methods: In order to assess attribution of causative factors in COPD by clinicians, we used 15 hypothetical cases of COPD, structured to represent a broad range of smoking and occupational exposure histories. Cases were developed a priori into nine categories: combinations of low, medium and high tobacco smoking and low, medium, and high COPD-risk occupational exposures. Twelve general experts in COPD and 12 specifically in occupational lung disease were invited to rate the cause of COPD in each case, attributing a percentage contribution to the harm caused by three categories: (i) smoking, (ii) occupational exposures and (iii) other causes. Results: To date, responses have been received from nine raters (seven occupational and two general). Ratings from a selected spectrum of cases are shown in Abstract P3 Table 1, expressed as median and IQR. Attribution varied with the degree of exposures, but even light smoking (less than 15 pack years) was weighted more heavily than substantial occupational exposure. Conclusions: There was a wide range of estimates relating to causative factors in COPD documented by experienced clinicians. These findings are consistent with the a priori assumption that attributing COPD causation in an individual case is difficult, as a sparse evidence base exists to guide clinicians. Further work is needed to allow translation of epidemiological findings to attribution in individual COPD cases, to better facilitate the screening, identification and management of occupational COPD.